“I think it is our responsibility, but not solely our responsibility”: A qualitative study exploring teachers’ perspectives on promoting mental health in Northwest London primary schools - Cecilia N. Ashu; Dougal S. Hargreaves; Tamsin Robinson; Dasha Nicholls; Bina Ram (PLoS ONE, 2025)
In England, 1 in 5 children and young people (CYP; aged 8–25 years) has a probable mental disorder with higher rates among those living in poverty, and among white children compared with other ethnic groups. However, in the UK, research shows that the prevalence of mental health conditions and associated service use differs among some ethnic minority groups (e.g., Asians) suggesting potential unmet mental health need. Early interventions have been shown to improve life outcomes, and UK government policies encourage the promotion of mental health and wellbeing in schools and colleges, but poor mental health continues to rise. Despite evidence showing that mental health problems occur as early as age 5 years, limited research focusses on primary schools (children aged 5–10 years). Northwest London (NWL), UK, is a diverse region in London, is in the top 20% most deprived, and has a high demand for CYP mental health services. The aim of our study was to explore teachers’ perspectives of promoting positive mental health in NWL primary schools. We created a semi-structured interview based on policy guidance. Nine teachers were recruited and interviewed during June and July 2024. Thematic analysis identified six overarching themes: (1) mental health needs; (2) responsibility; (3). factors contributing to poor mental health; (4). barriers and (5) facilitators to providing support; and (6) collaboration. Subthemes included lack of skills to address the broad spectrum of mental health needs, funding, resources, and lack of support systems to ensure all children receive the right support at the right time. Our study highlights implementation gaps for promoting mental health policy in diverse real-world settings, and suggests that whilst schools play an important role for early mental health intervention, wider complexities limit sufficient support provision. Our findings have potential implications for mental health promotion policies in school settings.